Bid Ask Spread, Market Value, Variance Return Terhadap Holding Period: (Faktor Determinan Periode Menahan Saham) - Rina Nurjanah; Eka Avianti Ayuningtyas; Sunita Dasman; Putri Nur Amalia (Politeknik Ganesha Medan, 2025)
This study aims to analyse the impact of bid-ask spread, market value, and variance return on the stock holding period. The bid-ask spread is a measure of transaction costs and liquidity. The market value reflects the size and stability of the company. Finally, the variance return shows the level of stock volatility. The data analysis was conducted on several energy sector companies traded on the stock market between 2019 and 2021. The research method employs descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, and determination coefficient testing. The results demonstrated that bid-ask spread and market value exert no significant influence on the holding period. Conversely, variance return has a significant negative effect on the holding period, indicating that the higher the variability of a stock's return, the shorter the stock's holding period by investors. This finding indicates that return volatility is an important factor that investors consider when deciding the duration of stock ownership. This study provides implications for investors to pay more attention to the level of stock volatility in their investment strategy and for market regulators to manage volatility to support better market stability.